IRS-assisted D2D system resource allocation and RCG beamforming optimization in H-CRAN - Xu, Xiaorong; Xue, Jishou; Wu, Jun; Bao, Jianrong (Dianxin Kexue, 2024)
Intelligent reflecting surface（IRS）-assisted device-to-device（D2D） communications in heterogeneous cloud radio access network（H-CRAN） were investigated as research background. Resource allocation and Riemannian conjugate gradient（RCG） beamforming optimization were studied, with the objective of system sum rate maximization. System sum rate was formulated as the optimization objective, which was subject to several constraint conditions such as sub-channel reuse coefficient, transmit power threshold, as well as the modulus of the IRS reflection coefficient. To solve the formulated mixed-integer non-linear programming problem, a channel-strength-based deferred acceptance algorithm was proposed to obtain channel reuse indicators. The problem was then decomposed into two subproblems. For transmit power optimization subproblem, successive convex approximation（SCA） was used to solve it. For IRS beamforming optimization subproblem, the beamforming vector constraint was transformed into a complex circular manifold and